(untitled) (International Research Journal on Islamic Studies (IRJIS), 2022)
Economics resources are indispensable for the development and survival of any country. Each country manages its own resources if they do not develop a consistent process and strategy of organization and development, then the economic condition of that falls into decline. This is an indisputable fact and can be observed in today’s world. The main purpose of this research is to introduce economic resources which are fundamental to the economic development of any country, then what teachings are found in the Qur’an and Hadis about these resources have been brought to the light. In this article the age of Hazrat Umar R.A is presented as an example, how economic resources were managed during that period and what steps were taken for their development, because the age of Hazrat Umar R.A was the best period in terms of economic development and in this modern age when our country is suffering from many economic resources, how can we benefit from it?